2008
DOI: 10.1159/000154785
|View full text |Cite
|
Sign up to set email alerts
|

Enamel Formation Genes Are Associated with High Caries Experience in Turkish Children

Abstract: There is evidence for a genetic component in caries susceptibility, and studies in humans have suggested that variation in enamel formation genes and their interaction with Streptococcus mutans levels may contribute to caries. For the present study, we used DNA samples collected from 173 unrelated children from Istanbul: 91 children with 4 or more affected tooth surfaces and 82 caries-free children. Six single-nucleotide polymorphism markers were genotyped in selected candidate genes (ameloblastin, amelogenin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
173
1
22

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 148 publications
(206 citation statements)
references
References 39 publications
10
173
1
22
Order By: Relevance
“…5,7,11 On the other hand, Patir et al observed an overrepresentation of the minor T allele in rs34538475 in caries experienced individuals in comparison to controls, regardless of the stage of the disease. 4 In our study, however, we observed an opposite association, as both the minor T allele (p < 0.0001) and the minor TT homozygote (p < 0.0001) were overrepresented in controls in comparison to cases with caries, which supported the T allele as a protective variant. There were no differences in allele and genotype frequency between caries experienced and caries-free children in rs4694075 for AMBN gene in our study.…”
Section: Discussioncontrasting
confidence: 65%
See 4 more Smart Citations
“…5,7,11 On the other hand, Patir et al observed an overrepresentation of the minor T allele in rs34538475 in caries experienced individuals in comparison to controls, regardless of the stage of the disease. 4 In our study, however, we observed an opposite association, as both the minor T allele (p < 0.0001) and the minor TT homozygote (p < 0.0001) were overrepresented in controls in comparison to cases with caries, which supported the T allele as a protective variant. There were no differences in allele and genotype frequency between caries experienced and caries-free children in rs4694075 for AMBN gene in our study.…”
Section: Discussioncontrasting
confidence: 65%
“…Patir et al observed an overrepresentation of the CC genotype in caries individuals (Turkish population), which is in contradiction with our results, where the major CC genotype turned out to be protective against caries occurrence. 4 On the other hand, Abbasoğlu et al found no association between the same AMELX polymorphism and caries susceptibility in Turkish children. 5 There were also no associations between amelogenin genetic variants and dental caries experience in other studies performed on Polish, French, Caucasian, and Japanese populations.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations